Methamphetamine psychosis in Australia, Philippines, and Thailand: Recommendations for acute care and clinical inpatient management - Robert Ali (2018)
Aim: Describe the management of patients with methamphetamine (MA)-induced psychosis and offer recommendations for effective treatment. Methods: Prospective assessment of consecutive admissions at 6 public psychiatric treatment services in Australia, the Philippines, and Thailand. One hundred and fifty patients (aged 17 to 48 y) who screened negative for lifetime history of schizophrenia and organic psychosis participated in the study. Results: Sixty-one percent of participants presented with their first MA psychosis episode. Most common lifetime psychotic symptoms were persecutory delusion (81%) and auditory hallucinations (77%) experienced on admission by 22% and 48%, respectively. Longer treatment duration associated with first episode MA psychosis; male; longer duration since last use MA before admission; more severe positive psychotic symptoms and more negative symptoms. One fifth of the patients continued experiencing psychotic symptoms at discharge. Conclusions: No consistent evidence-based guidelines exist. In their absence, the authors suggest clinical management should include careful frontline sedation, judicious second-generation antipsychotics treatment and relapse prevention support in the community. Copyright© 2010 by Lippincott Williams & Wilkins.